Avaliação do uso do Tiazoacetilpirimida 04 (TAP – 04) no tratamento experimental de cães com infecção natural por Leishmania infantum - NAKASONE, Eiji Kevin Nakasone (2020)
Currently, the treatments used for Canine Visceral Leishmaniasis are varied and with different results, which include leishmanicidal, leishmaniostatic drugs, immune system modulators, in addition to supportive therapy to control complications secondary to the disease. Due to the adverse reactions to the different treatment protocols for canine disease, it is important to search for new treatments. Therefore, the objective of this work was to evaluate the use of Tiazoacetylpyrimide 04 in the treatment of dogs with natural infection by Leishmania infantum. For this purpose, six dogs were used, which received TAP - 04 at a dose of 1 mg/kg once a week for 12 weeks. The animals were monitored weekly through clinical, hematological, biochemical, and parasitic load determination. On day zero all animals presented lymphadenomegaly, apathy and dermatopathy. The hematological results revealed that 83.33% (5/6) presented anemia, 33.33% (2/6) of the normochromic normocytic type, 16.67% (1/6) normochromic microcytic, and 33.33% (2 / 6) normochromic macrocytic. Regarding the leukocyte profile, 83.33% (5/6) presented leukopenia, 66.67% (4/6) lymphopenia, 33.33% (2/6) neutropenia, 16.67% (1/6) eosinophilia, a decrease in the number of platelets was observed in 50% (3/6), hyperproteinemia in 83.33% (5/6) and 100% presented hypoalbuminemia and hyperglobulinemia. The monitoring of the treatment showed that there was no significant difference in the clinical scores of the animals studied, however, up to 60 days after the treatment, an improvement in the hematological and biochemical tests was observed. The evaluation of the parasitic load has shown a decrease of 30% in animals donated to date 60. In this sense, new studies need to be carried out with a greater number of animals as well as with a longer follow-up to evaluate the response of animals with natural infection by L. infantum submitted to treatment with TAP - 04.